Effects of Naringenin (NG) as an Anti- Proliferative and Anti-Apoptotic Factor on ER Alpha and ER Beta in PCOS - Fardad Saremi; Fatemeh Parvin Sabet; Kimia Nabiee; Fatemeh Tolouei; Kooshyar Kouchaki; Mahya Yasami; Shaghayegh Soltani; Reza Zandi; Mona Gorji (Advanced Biomedical Research)
Background: Polycystic ovary syndrome (PCOS) is the most prevalent endocrine disorder among women of reproductive age, characterized by elevated androgen levels, chronic inflammation, and oxidative stress. This research investigated the therapeutic impact of Naringine (NAR) on antioxidant and anti-inflammatory factor levels in the ovarian tissues of rats diagnosed with PCOS. Materials and Methods: Forty two mature (6–8 weeks old) female wistar rats were assigned into six groups (seven rats in each group), including control, PCOS-induced (PCOS like condition was induced based on the previous study, control with a dose of 20 mg/kg, control with a dose of 40 mg/kg, PCOS-induced with a dose of 20 mg/kg, PCOS-induced with a dose of 40 mg/kg groups. After 21 days of intervention, the animals were euthanized. The serum levels of sex hormones (estrogen, progesterone) and androstendion were measured. Ovary samples were also collected for RNA extraction, which was done to compare the expression levels of the Erα and Erβ among groups. Results: Treatment with Naringine significantly increased the total antioxidant capacity (TAC), superoxide dismutase (SOD), glotathion peroxidase (GPX) and while decreasing malondialdeyide (MDA) level. Additionally, it increased estrogen and progestone concentration and decreased androstendion concentration. Moreover, the level of gene expression and production of ER-a and ER-b proteins significantly increased in the groups treated with Naringine. Conclusion: Naringine can be considered a potent antioxidative and antiapoptotic agent for therapeutic strategies in reproductive and regenerative medicine. These findings suggest that Naringine could be a potential candidate for the treatment of PCOS disorders.